2015
DOI: 10.1021/acs.jpcc.5b03521
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Synthesis of Hierarchical Multiple-Growth-Hillock Superstructures of Silver Nanoparticles on ZnO

Abstract: Hierarchical superstructures of Ag nanoparticles with novel morphology resembling multiple growth hillocks were synthesized for the first time using photochemical method through the screw-dislocation-driven, nanoparticle-mediated crystal growth mechanism. The Ag nanoparticles were in situ synthesized from the photoreduction of Ag + ions adsorbed on ZnO. The absence of organic capping agents in the synthesis protocol makes this photochemical approach suitable for preparing metal/semiconductor hybrid materials w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…We have recently reported that short-time (less than 10 min) UV illumination would yield multiple-growth-hillock-like superstructures of nanoparticles on ZnO. 23 The nanoparticle-mediated crystallization process was governed by screw dislocations under relatively low supersaturation. Note that the volume of the reaction solution is only about 100–200 μL.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have recently reported that short-time (less than 10 min) UV illumination would yield multiple-growth-hillock-like superstructures of nanoparticles on ZnO. 23 The nanoparticle-mediated crystallization process was governed by screw dislocations under relatively low supersaturation. Note that the volume of the reaction solution is only about 100–200 μL.…”
Section: Resultsmentioning
confidence: 99%
“…(A) Small nanoplates obtained at 10 min, coexisting with the multiple-growth-hillock-like superstructures. 23 (B) Small nanoplates obtained at 30 min. (C) Close-up view of the small nanoplates obtained at 30 min.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations